The dramatic and the poetic in Le Concile Féerique by Jules Laforgue - Oliveira, Andressa Cristina de (Lettres Françaises, 2011)
We briefly present here a dramatic work of the French Symbolist poet Jules Laforgue – Le Concile Féerique. During the analysis, we see collages of Fleurs de bonne volonté poems, conceived in a dialogued and original way, showing us, mostly, in the work of the French poet, the modernity and the persistence of poetry.